Determining optimal gestational weight gain (GWG) in a northwest Chinese population: A CONSORT. Issue 21 (28th May 2021) - Bai, Yang; Li, Lanlan; Wang, Baolin; Qiu, Jie; Ren, Yucheng; He, Xiaochun; Li, Yilin; Jia, Yanfeng; He, Chunxiao; Cui, Hongmei; Lv, Ling; Lin, Xiaojuan; et al.
Abstract : Abstract: To determine optimal gestational weight gain (GWG) for the Chinese population. Live singleton deliveries at the largest maternal & childcare hospital in northwest China from 2010 to 2012 were analyzed retrospectively. Multivariable logistic regression analysis was conducted to determine the lowest aggregated risk of interested perinatal outcomes based on Chinese adult body mass index (BMI) categories. Eight thousand eight hundred seventy enrolled parturients were divided into 4 groups according to their prepregnancy BMI: underweight (21.31%, BMI < 18.5 kg/m 2 ), normal weight (67.81%, 18.5 kg/m 2 ⩽ BMI < 24 kg/m 2 ), overweight (8.99%, 24 kg/m 2 ⩽ BMI < 28 kg/m 2 and obese (1.89%, BMI ≥ 28 kg/m 2 ). The optimal GWG values for the above 4 groups were 16.7 kg (GWG range, 12.0–21.5), 14.5 kg (9.5–19.5), 11.5 kg (7.0–16.5), and 8.0 kg (5.0–13.0). The rates of inadequate, optimal and excessive GWG in present study were 6.14% (545), 62.34% (5529), and 31.52% (2796) respectively, which were significantly different from those of the 2009 Institute of Medicine recommendation (χ 2  = 1416.05, Pinteraction < 0.0001). Wider optimal GWG ranges than those recommended by Institute of Medicine were found in our study, and our proposed criteria seems to be practical to the Chinese population.